Unilateral biportal endoscopy vs. open decompression for lumbar epidural lipomatosis-cohort study using a prospective registry - Tan, Bing; Zheng, Yu-hao; Lei, Chao; Ouyang, Jian-yuan; Wen, Yan-bo; Shi, Zhuo-hua; Yang, Qi-Yuan (Frontiers in Neurology, 2024)
Objective: This study aimed to compare the outcomes of unilateral biportal endoscopy, unilateral laminectomy bilateral decompression (UBE-ULBD), and open lumbar decompression (OLD) in patients with lumbar epidural lipomatosis (LEL). Methods: This prospective observational study was conducted from March 2019 to May 2022 and encompassed 33 patients with LEL who underwent lumbar decompression. The study included 15 cases of UBE-ULBD decompression and 18 cases of open decompression, which were followed up for one year.Radiographic evaluation included the cross-sectional area (CSA) of the thecal sac and paraspinal muscles on MRI. Clinical results were analyzed using the Short Form-36 Score (SF-36), the Numeric Pain Rating Scale (NRS) for lumbar and leg pain,creatine kinase,the Roland and Morris Disability Questionnaire (RMDQ), and the Oswestry Disability Index (ODI). Results: The dural sac CSA increased considerably at the 1-year postoperative follow-up in both groups (p < 0.001). The operative duration in the OLD group (48.2 ± 7.2 min) was shorter than that in the UBE-ULBD group (67.7 ± 6.3 min, p < 0.001). The OLD group (97.2 ± 19.8 mL) was associated with more EBL than the UBE-ULBD group (40.6 ± 13.6 mL, p < 0.001). The duration of hospitalization in the OLD group (5.4 ± 1.3 days) was significantly longer compared with the UBE-ULBD group (3.5 ± 1.2 days, p < 0.01). The SF-36, NRS, RMDQ, and ODI scores improved in both groups postoperatively (p < 0.001). Serum creatine kinase values in the UBE-ULBD group (101.7 ± 15.5) were significantly lower than those in the OLD group (330.8 ± 28.1 U/L) one day after surgery (p < 0.001). The degree of paraspinal muscle atrophy in the UBE-ULBD group (4.81 ± 1.94) was significantly lower than that in the OLD group (12.15 ± 6.99) at one year (p < 0.001). Conclusion: UBE-ULBD and OLD demonstrated comparable clinical outcomes in treating LEL. However, UBE-ULBD surgery was associated with shorter hospital stays, lower rates of incision infection, lighter paravertebral muscle injury, and lower EBL than OLD surgery. Consequently, UBE-ULBD can be recommended in patients with LEL if conservative treatment fails.